Association between group cohesion and pre-competition mood states in youth athletes - Foschiera, Diogo Bertella; Stefanello, Joice Mara Facco; Legnani, Rosimeide Francisco Santos; Legnani, Elto (Cuadernos de Psicología del Deporte, 2022)
The purpose of this study is to analyze the possible associations of group cohesion and pre-competition mood states of youth athletes. This is a cross-sectional and quantitative study. The sample was composed of 81 athletes from both sexes, who practice collective modality sports, with average of age of 15.8±1.0 years. Data was collected through the Group Environment Questionnaire and POMS Inventory – Reduced, on the week prior to the athletes’ participation in state competitions. Spearman's correlation coefficient and binary logistic regression were used to analyze the data. The results indicate positive and significant correlations of group cohesion dimensions (p<0.05) with the vigor mood dimension, and negative and significant correlations (p<0.05) with tension, depression, anger, fatigue and confusion dimensions. Both group cohesion types (social and task) significantly predicted the mood state profiles. The highest predictive statistical indicator was presented by task cohesion (OR=2.481; IC=1.477-4.167; p<0.001). The results found offer evidence to confirm the prior expectation that higher levels of group cohesion are associated with better pre-competitive mood states profiles in youth athletes. The results suggest that higher group cohesion levels can affect positively the pre-competition mood states in youth athletes.